Proposição de um método sistêmico para melhoria da cooperação interdepartamental de uma empresa de manufatura do ramo metal mecânico - Machado, Mateus dos Santos (Universidade do Vale do Rio dos Sinos, 2015)
If an organization is made up of several parts working towards a common goal, it is assumed that the cooperation among the several parts of the organization is essential for its operation. Nevertheless, empirical evidence shows that cooperation is an issue for many organizations. While acknowledging the importance of cooperation for the organizations, the current literature lacks methods that indicate how to reach it. In this context, this research aims to propose a systemic method for analyzing the system of indicators and mental models aimed at improving interdepartmental cooperation in a manufacturing company at the mechanical metal industry. The method approach used was Design Science Research, which is characterized as a process that uses knowledge to design artifacts aimed at the solution of specific problems, not necessarily the optimal solution, but a satisfactory solution to the situation. Firstly, the problems involved in this study were conceptualized, following the theoretical framework with the approach of the main topics for the research development, as the method is sketched and later applied at a large manufacturing company of the mechanical metal industry. At the end, an assessment was made, seeking evidence of the applied method and its effectiveness to meet the objectives. The results, reported improvement and the testimony of the participants indicate that the proposed method allows us to propose actions to enhance interdepartmental cooperation as it is approached systemically.
Keywords: Cooperação interdepartamental; Conflito; Método sistêmico; Interdepartmental cooperation; Conflict; Systemic method; ACCNPQ::Engenharias::Engenharia de Produção